Multicomponent self-assembly based on bioactive molecules of traditional Chinese medicine (TCM) - Liangchun Li; Renlin Zheng; Rongqin Sun (Elsevier, 2022)
In traditional Chinese medicine (TCM), medicinal materials such as herbal are mostly used as complex prescription, which composed of a variety of bioactive molecules. The different compounds mostly showed different noncovalent interactions including H-bond, electrostatic attraction, hydrophobic and hydrophilic interactions, which could form supramolecular structures. In this review, we will focus on multi-component self-assembly based on the bioactive components of TCM, the structures and morphologies of which are controlled by the special noncovalent interactions, to show the recent developments in the field of multi-component self-assembly. At the end, the applications and shortcomings of current using multi-component self-assembly tact to study pharmacodynamics substance basis of TCM are discussed, which should promote the process of modernization of TCM.